Hodnocení finanční situace podniku a návrhy na její zlepšení - Zimčíková, Eva (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Bakalářská práce hodnotí finanční situaci společnosti KASKO, spol. s r.o. v období let 2002 až 2005 pomocí vybraných ukazatelů finanční analýzy. Analyzuje problémy a navrhuje možná řešení, která povedou ke zlepšení finanční situace podniku do budoucna a ke zkvalitnění rozhodovacích procesů v oblasti operativního i strategického řízení.

Batchellor’ s thesis evaluates financial situation of the firm KASKO spol. s r.o. within the period of years 2002 and 2005, by selected indicators of the financial analyzes. It analyzes problems and proposes possible solutions, which will lead to the improvement of the company financial situation in the future and better quality of decision making processes in the area of operative and strategic management.
Evaluation of Company Financial Performance and Proposals of its Improvement
Keywords: Finanční situace; společnost; SWOT analýza; finanční analýza; strategie; finanční ukazatele; problémy; návrhy.; Financial situation; company; SWOT analyzes; financial analyzes; strategy; financial indicators; problems; proposals.